VIV regimes and simplified solutions by the spectral model description. Issue 198 (March 2020) - Pagnini, L.C.; Piccardo, G.; Solari, G.
Abstract: The present paper discusses technical aspects of the vortex-induced vibrations (VIVs) of structures excited by the wind in the framework of the spectral model, which is applied by many codes and guidelines for civil engineering verifications. Quantitative thresholds related to Scruton number domains, where the structural response can be considered in "forced vibration" or "lock-in" regime, are proposed. In this way, the type of VIV response and its evaluation can be assessed with simple calculations that use the parameters already present in codes and guidelines. An analytical solution of the original model allows straightforward evaluations inclusive of operative criteria to properly consider structural and flow conditions concerning the coefficients governing the VIV response in the spectral description, leaving out some assumptions that are commonly adopted. Extensive numerical applications, limited here to circular cylinders and including a real full-scale chimney, allow to identify the most significant parameters of the model and the criticalities connected with their choice. Highlights: Domains of validity for VIV "forced vibration" and "lock-in" regime. Closed-form solution of the wake forcing parameter governing VIV response. Identification of parameters influencing "forced vibration" VIV response. Comparisons between approximate and complete VIV solutions.